2011
DOI: 10.2118/129877-pa
|View full text |Cite
|
Sign up to set email alerts
|

Snorre Low-Salinity-Water Injection—Coreflooding Experiments and Single-Well Field Pilot

Abstract: Summary Low-salinity (lowsal) waterflooding has been evaluated for increased oil recovery (IOR) at the Snorre field. Coreflooding experiments and a single-well chemical tracer-test (SWCTT) field pilot have been performed to measure the remaining oil saturation after seawaterflooding and after lowsal flooding. The laboratory coreflooding experiments conducted at reservoir and low-pressure conditions involved core material from the Upper and Lower Statfjord and Lunde formations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(83 citation statements)
references
References 30 publications
2
81
0
Order By: Relevance
“…Several oil companies, such as BP [34], Shell [35], Saudi Aramco [36], and PetroChina [17,18,21,37] have conducted numerous lab experiments, i.e., Log-Inject-Log, Single Well Chemical Tracer Test (SWCTT), and field scale trials. Their results have shown that, while in some cases LSWF has achieved an additional 5-25% oil recovery, in other cases, only minor incremental oil recovery was observed [38].…”
Section: Introductionmentioning
confidence: 98%
“…Several oil companies, such as BP [34], Shell [35], Saudi Aramco [36], and PetroChina [17,18,21,37] have conducted numerous lab experiments, i.e., Log-Inject-Log, Single Well Chemical Tracer Test (SWCTT), and field scale trials. Their results have shown that, while in some cases LSWF has achieved an additional 5-25% oil recovery, in other cases, only minor incremental oil recovery was observed [38].…”
Section: Introductionmentioning
confidence: 98%
“…Saturating rock with the oil may cause the rock to become more oil-wet through a variety of brine/oil/rock interactions [6]. LSW studies on sandstones conclude that a high oil recovery is observed in rocks that are weakly waterwet [3,7]. LSW alters the wettability of the sandstones from an oil-wet state towards an optimum weakly water-wet state, thereby leading to an improved recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we really have one phase flow (in absence of water). The wettability of rock formation from the Snorre field is classified as neutral-wet to weakly water-wet (Skrettingland et al, 2011).…”
Section: Snorre Field Descriptionmentioning
confidence: 99%
“…The main sand interval porosity is 0.30 and the initial water saturation (S w ) is in the range of 0.1 -0.2. Three single well chemical tracer (SWCT) tests have been carried out in Well P-07 which in each test, three tracers (Ethyl acetate (EtAc) as a primary and reactive tracer which produces Ethanol (EtOH) as a fourth tracer, n-propanol (NPA) as a backup tracer for EtAc if the amount of remained EtAc be negligible after hydrolysis reaction, and isopropanol (IPA) tracer for material balance proposes) were injected in order to evaluate the effect of injection of seawater, drill water, and low salinity (Skrettingland et al, 2011).…”
Section: Snorre Field Descriptionmentioning
confidence: 99%
See 1 more Smart Citation